Deep anthropogenic impacts on benthic marine diversity of the Humboldt Current Marine Ecosystem: Insights from a Quaternary fossil baseline - Rivadeneira, Marcelo M.; Nielsen, Sven N. (Frontiers in Marine Science, 2022)
The Humboldt Current Marine Ecosystem (HCE) is one of the most productive areas in the global ocean, but current anthropogenic stressors, particularly overfishing, pose a significant threat to marine biodiversity. Moreover, the limited time scale of modern assessments may underestimate the magnitude of the human alterations to marine biodiversity. Here we use the rich Quaternary fossil record present along the HCE coast, encompassing the last ca. 500 kyr, to build a baseline to evaluate the impact of human activities on the diversity of mollusk assemblages. We compiled an extensive database of >13,000 occurrences and ca. 370,000 individuals of 164 species of gastropod and bivalves from modern and fossiliferous outcrops from southern Peru to northern Chile (15-30ºS). We tested for changes in coverage-based species richness, species dominance, species composition (Chao dissimilarity, unweighted and weighted by abundance), and the relative abundance (i.e., the proportion of individuals) of species exploited by the artisanal fisheries. Comparisons between fossil and modern assemblages were carried out at different scales of spatial aggregation to buffer against inherent differences in spatial and temporal averaging. Species composition shows remarkable stability in fossil assemblages, from Middle Pleistocene to Holocene, at most scales of spatial aggregation. Modern assemblages showed drastic alterations compared to fossil counterparts when analyses considered spatial aggregation scales, i.e., significant changes in species composition, and a 3 to 6-fold reduction in the relative abundance of exploited species, but not changes in species richness and dominance. Results suggest that contemporaneous anthropogenic activities disrupted a long-term stability in the species composition. The diversity of modern mollusk assemblages is unseen in the past 500 kyr and seems deeply perturbed by overfishing. Our synthesis set the foundations for a conservation paleobiology approach to robustly understand the impacts of anthropogenic stressors at the HCE.